Analysis of acrobatic tumbling exercises on floor and balance beam - Knoll, Kl. (2000)
The same biomechanical mechanisms - the reduction of the angular momentum in the somersault take-off when the somersault is preceded by rondat, flic-flac act on the floor and the balance. On the balance beam the acrobatic tumbling combination rondat, flic-flac, somersault variant only produces about 40 % of the kinetic energy compared with the floor. Thus the angular momentum provided by the somersault and the driving height are smaller than on the floor. The degree of difficulty on the balance beam can therefore only be enhanced to a limited extend despite the almost identical flight time with the floor.